China's role in the regional and international management of Korean conflict: an arbiter or catalyst? - BELDER, FERİT; MEHMETCİK, HAKAN (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2018)
There are diverging assessments of China's role in resolving the nuclear crisis on the Korean Peninsula. China's role has been characterised variously as a bystander, arbiter, catalyst and mediator over the years. This paper aims to clarify where China stands on North Korea and assesses the different phases of the Chinese approach to conflict resolution during the North Korean nuclear crisis. The main argument is that China wishes to maintain the regional status quo while appearing to adjust its position in line with the international community. China's current duplicity stems from its different priorities and concerns to the remainder of the world, and can best be explained using a role theory analysis.
Keywords: China; North Korea; role theory; North Korean nuclear crisis; conflict management; POLICY